Riboregulators: Fine-Tuning Virulence in Shigella - Fris, Megan E.; Murphy, Erin R. (Frontiers in Cellular and Infection Microbiology, 2016)
Within the past several years, RNA-mediated regulation (ribo-regulation) has become increasingly recognized for its importance in controlling critical bacterial processes. Regulatory RNA molecules, or riboregulators, are perpetually responsive to changes within the micro-environment of a bacterium. Notably, several characterized riboregulators control virulence in pathogenic bacteria, as is the case for each riboregulator characterized to date in Shigella. The timing of virulence gene expression and the ability of the pathogen to adapt to rapidly changing environmental conditions is critical to the establishment and progression of infection by Shigella species; ribo-regulators mediate each of these important processes. This mini review will present the current state of knowledge regarding RNA-mediated regulation in Shigella by detailing the characterization and function of each identified riboregulator in these pathogens.